Trends in care processes and survival following prehospital resuscitation improvement initiatives for out-of-hospital cardiac arrest in British Columbia, 2006–2016 - Grunau, Brian; Kawano, Takahisa; Dick, William; Straight, Ronald; Connolly, Helen; Schlamp, Robert; Scheuermeyer, Frank X.; Fordyce, Christopher B.; Barbic, David; Tallon, John; Christenson, Jim (Resuscitation, 2018)
British Columbia (BC) Emergency Health Services implemented a strategy to improve outcomes for out-of-hospital cardiac arrest (OHCA), focusing on paramedic-led high-quality on-scene resuscitation. We measured changes in care metrics and survival trends. This was a post-hoc study of prospectively identified consecutive non-traumatic ambulance-treated adult OHCAs from 2006 to 2016 within BC’s four metropolitan areas. The primary outcome was survival to hospital discharge; we also described available favourable neurological outcomes (mRS ≤3). We tested the significance of year-by-year trends in baseline characteristics, and calculated risk-adjusted survival rates using multivariable Poisson regression. We included 15 145 patients. In univariate analyses there were significant increases in bystander CPR, chest compression fraction, advanced life support attendance, duration of resuscitation until advanced airway placement, duration of resuscitation until termination, and overall scene time. There was a significant decrease in initial shockable rhythms, bystander witnessed arrests, and transports initiated prior to ROSC. Survival and the proportion of survivors with favourable neurological outcomes increased significantly. In adjusted analyses, there was an improvement in return of spontaneous circulation (risk-adjusted rate 41% in 2006 to 51% in 2016; adjusted rate ratio per year 1.02, 95% CI 1.01–1.02, p < 0.01 for trend) and survival at hospital discharge (risk-adjusted rate 8.6% in 2006 to 16% in 2016; adjusted rate ratio per year 1.05, 95% CI 1.04–1.06, p < 0.01 for trend). From 2006 to 2016 BC’s provincial ambulance system prioritized paramedic-led on-scene resuscitation, during which time there were significant improvements in patient outcomes. Our data may assist other systems, providing a model for prehospital resuscitation quality improvement.